Maternal exposure to Cochlospermum regium: a toxicological evaluation - Cunha-Laura,Andréa Luiza (2013)
Cochlospermum regium (Schrank) Pilg., Bixaceae, is a Brazilian plant widely used as a folk medicine in the southwestern of the Brazil to treat inflammation and infection diseases. However, the effects of C. regium hydroethanolic extract on pregnant rats have not been assessed. To evaluate the effects of the C. regium on pregnant rats during the organogenic period, the hydroethanolic extract was administered via gavage at a dose of 11.5 mg/kg/day to rats from 6th to 15th day of pregnancy. No clinical signs of maternal toxicity were observed. The placenta's and fetuses' weight were similar in control and treated animals. The term fetuses dis not present malformations or anomalies although the number of live fetuses and birth rate were significantly decreased. In conclusion, the C. regium hydroethanolic extract is nontoxicant to the pregnant rat although it would be likely to interfere in the progress of the embryofetal development.